2006
DOI: 10.1002/jcb.20797
|View full text |Cite
|
Sign up to set email alerts
|

High glucose increases extracellular matrix production in pancreatic stellate cells by activating the renin–angiotensin system

Abstract: Pancreatic stellate cells (PSCs) are involved in pancreatic inflammation and fibrosis. Recent studies have shown that blocking the renin-angiotensin system (RAS) attenuates pancreatic inflammation and fibrosis. However, there are few data about the direct effects of high glucose on extracellular matrix (ECM) protein synthesis and angiotensin II (Ang II) induction in PSCs. PSCs were isolated from male Sprague-Dawley rats and cultured in medium containing 5.5 mM (LG group) or 27 mM D-glucose (HG group). Levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 44 publications
3
63
1
1
Order By: Relevance
“…In addition, in vitro studies showed that high concentration of glucose (which can result from sucrose feeding) induced pancreatic stellate cell (PSC) proliferation, resulting in increased extracellular matrix production and a consequent aggravation of fibrosis (37,38). High glucose and high insulin have been reported to have an additive effect on the activation and proliferation of rat PSCs (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vitro studies showed that high concentration of glucose (which can result from sucrose feeding) induced pancreatic stellate cell (PSC) proliferation, resulting in increased extracellular matrix production and a consequent aggravation of fibrosis (37,38). High glucose and high insulin have been reported to have an additive effect on the activation and proliferation of rat PSCs (39).…”
Section: Discussionmentioning
confidence: 99%
“…22 The diabetic environment provides numerous signals which could lead to stellate cell activation. Thus, previous studies using classical PSCs have demonstrated that hyperglycemia, 16,31 activation of the RAS, 32 oxidative stress, 17,30 platelet-derived growth factors, 33 and inflammatory cytokines 34 all enhance PSC activation and proliferation. The environment of the diabetic islet is characterized by the presence of the hyperglycemia [35][36][37] and oxidative stress, [38][39][40] as well as macrophage infiltration and increased expression of inflammatory molecules such as IL-1, IL-6, TNF-α, MCP-1, and MIP-1α.…”
Section: -1227mentioning
confidence: 96%
“…Hyperglycemic conditions activate PSC with a parallel increased production of Ang II (50), and RAS blockade through candesartan or ramiprilat suppress the expression of extracellular matrix proteins in cultured rat PSC (50). More recently, not only high glucose concentrations but also high insulin concentrations were shown to activate PSC, probably through MAPK pathway activation (38).…”
Section: Islet Fibrosismentioning
confidence: 97%